MINI RISET: POTENSI CEMARAN MIKROPLASTIK DI PANTAI TEMBERAN, KABUPATEN BANGKA - Lestari, Winda; Citra, Wallika; Putri, Yussi; Kurniawan, Andri (Program Studi Akuakultur, Universitas Bangka Belitung, 2024)
The presence of microplastics in the environment has generated global concerns. Microplastics contamination is a global environmental problem which negative effect in a habitat, include waters and can enter the food chain that contribute to human health. Occurrence of microplastics in the environment affected by intensive anthropogenic activities, one of them is tourism activity. This study aimed to determine the types and the abundance of microplastics at Temberan Beach, Bangka Regency, Bangka Belitung Archipelago Province. The water samples were taken using a plankton net (mesh size 100 / 150 µm) with diameter 15 cm and 1,5 L of the surface of the water was analyzed the microplatics content. The microplasctics analysis was carried out by oxidative digestion of organic matters method which are utilizing hydrogen peroxide (H2O2). The results showed there were four types of microplastics and their abundance, namely fiber (54%), foam (26%), fragment (15%), and film (5%). We have observed that anthropogenic activity contributed to microplastic abundance.